Vocabulary Mastering of Hanyu Shuiping Kaoshi Level 3 Students of Chinese Language and Culture Study Program Hasanuddin University - Yuspani Amelia J; Wan Wen Bin; Fakhriawan Fathu Rahman (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research examines and contains a description of the mastery of Mandarin vocabulary at the level of Hanyu Shuiping Kaoshi 3 students of the Mandarin Language and Chinese Culture study program at Hasanuddin University using a psycholinguistic approach by taking a sample of 20 students from a total population of 40. The description regarding mastery of vocabulary is divided into two, namely mastery of receptive vocabulary and mastery of productive vocabulary by carrying out two types of tests, the first test is a written test which consists of six parts which all require abilities which include: knowledge, understanding and use of one character, a combination character characters that form words and vocabulary contained in a sentence based on a certain context or idea, then second test is an interview test to describe the factors that influence mastery of this vocabulary which divided into two, namely the internal factor which included the curiosity, certain positive activity, self-learning methods, and intrinsic and extrinsic motivation, therefore the external factor which included social environment and the availability of learning media. This research come to the conclusion of the vocabulary as essentially unmeasurable and was shown as the form of knowledge which going through mental processes, from a continuum stage of being able to receiving, absorbing and comprehend vocabulary towards a continuum stage of being able to use and producing vocabulary as known as the receptive knowledge to productive knowledge.